P0471DIALYSIS TREATMENT AT THE TIME OF DIAGNOSIS PREDICTS OUTCOMES IN ANCA ASSOCIATED VASCULITIS PATIENTS - DATA FROM CROATIAN REFERRAL CENTER. (6th June 2020) - Crnogorac, Matija; Brechelmacher, Ana; Horvatić, Ivica; Kacinari, Patricia; Tišljar, Miroslav; Toric, Luka; Durlen, Ivan; Juric, Klara; Senjug, Petar; Galešić Ljubanović, Danica; Galesic, Kresimir
Abstract: Background and Aims: Dialysis dependence and ESRD are known complications of ANCA associated vasculitis (AAV) with renal involvement. What is not so often discussed is the role of dialysis treatment at the time of diagnosis and how it affects patient outcomes as well as characteristics of such patients. We present data showing the importance of dialysis treatment at the time of diagnosis as the predictor of clinical outcomes. Method: This study included 106 consecutive AAV patients with renal involvement in the period from 2007-2017. We performed renal biopsy on patients using automatic 16 Gauge needle. Light, immunofluorescent and electronic microscopy were performed. Primary outcomes were combined outcome progression to end-stage renal disease, defined as persistent (more than three months) need for renal replacement therapy or permanent reduction of EGFR to <15ml/minute (according to CKD EPI formula) and/or death (ESRDD), death (D) and ESRD alone, and disease relapse. Kaplan Meyer survival analysis and multivariate Cox proportional hazard regression analysis were used to explore difference between phenotypes and finding significant predictors regarding outcomes. Results: Out of 106 patients (55, 6% female, median age 61; IQR 51-70) there were 66 (61, 1%) microscopic poliangitiis (MPA), 20 (18, 5%) granulomatosis with angitiis and 20 (18, 5%) with renal limited vasculitis (RLV). Out of those 14 (13%) were PR3-ANCA positive patients, 57 (52, 8%) MPO ANCA positive, 5 (4, 6%) PR3-ANCA+MPO-ANCA positive and 32 (29, 6%) ANCA negative patients. Average serum creatinine (SCr) levels was 316, 5 μmol/l (IQR 207, 0-548, 5), 24-hour proteinuria median was 1, 7g/24h (IQR 0, 8-2, 8). According to the Berden classification 43 (39, 8%) patients had crescentic, 19 (17, 6%) focal, 34 (31, 5%) mixed and 12 (11, 1%) sclerotic class. Follow up time ranged from 1 to 127 months. Median follow up time was 21 months (IQR = 7-44). Median time to diagnosis was 3 months (IQR 2, 0-6, 0). Patients requiring dialysis treatment at the time of diagnosis were more often MPO – (p=0, 04), had more severe anemia (p=0, 001), higher CRP (p=0, 003), and more pronounced hypoalbuminemia (serums albumin <30g/l; p=0, 006).Such patients were older than those not requiring dialysis (p=0, 055) na had shorter time to diagnosis (p=0, 001). Clinically such patient s presented more often with RPGN (p<0, 001) which is in a way expected thus having higher SCr levels (p=<0, 001). Histologically dialysis treated patients predominantly had crescentic class, while non-dialysis group had focal class (p<0, 001). Of note dialysis group had more acute tubular damage (p=0, 007). Interestingly enough there was slightly more positive C3 deposition in dialysis group (p=0, 09). In univariate analysis the need for acute dialysis at the time of diagnosis of AAV was significant predictor for combined ESRDD, D, ESRD and relapse rate. In multivariate analysis the need for acute dialysis at the time of diagnosis of AAV remained significant predictor for ESRD (HR = 4, 674, 95% CI =1, 996-10, 946; p = < 0, 001) and relapse rate (HR = 59, 545, 95% CI =3, 467-1022, 665; p = 0, 005). Conclusion: The need for dialysis at the time of AAV diagnosis is a strong predictor for ESRD and relapse rate. It is also interesting to further study differences between patients needing dialysis at the time of diagnosis and those who don't need it.